2019
DOI: 10.1074/jbc.ra118.006189
|View full text |Cite
|
Sign up to set email alerts
|

KGF-1 accelerates wound contraction through the TGF-β1/Smad signaling pathway in a double-paracrine manner

Abstract: Edited by Jeffrey E. Pessin KGF-1 plays an important role in the wound healing process. Loss of the KGF-1 gene in diabetic mice attenuated the process of wound contraction, suggesting that KGF-1 contributes to wound contraction. However, the mechanism remains unclear. To investigate the role of KGF-1 in diabetic wound contraction, we established a keratinocyte-fibroblast co-culture system. Concentrations of transforming growth factor ␤1 (TGF-␤1) in conditioned supernatant treated with KGF-1 (KGF-1 group), tk;4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Therefore, we concluded that grafted cells could not directly participate in granulation tissue formation, but some components in the tissue suspension solution stimulate the development of granulation tissue. The extracellular components in the solution may contain cytokines [ 26 ], growth factors [ 6 , 27 , 28 ], proteinases [ 29 ] and matrix components [ 30 ], which include tumor necrotic factor, interleukins-1 and 6, transforming growth factor (TGF)-β, vascular endothelial growth factor, FGF, platelet-derived growth factor, epidermal growth factor, hepatocyte growth factor and matrix metalloproteinases, as well as collagens and collagen-derived proline-hydroxyproline peptides [ 31 , 32 ]. All of these factors are candidates of paracrine factors for wound-healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we concluded that grafted cells could not directly participate in granulation tissue formation, but some components in the tissue suspension solution stimulate the development of granulation tissue. The extracellular components in the solution may contain cytokines [ 26 ], growth factors [ 6 , 27 , 28 ], proteinases [ 29 ] and matrix components [ 30 ], which include tumor necrotic factor, interleukins-1 and 6, transforming growth factor (TGF)-β, vascular endothelial growth factor, FGF, platelet-derived growth factor, epidermal growth factor, hepatocyte growth factor and matrix metalloproteinases, as well as collagens and collagen-derived proline-hydroxyproline peptides [ 31 , 32 ]. All of these factors are candidates of paracrine factors for wound-healing.…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblast, a well-known phenotype of fibroblasts, carries α-SMA fibers, by which wounds can be contracted [ 27 ]. Cells are differentiated from resident tissue fibroblasts and/or blood-borne fibrocytes, and can be stimulated by various inflammatory factors, such as chemokines [ 35 ] and growth factors, especially TGF-β [ 27 , 36 ]. In our study, they were located in the upper area of granulation tissue, but not in the areas of contracted epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KGF has been shown to protect epithelial cells from the toxic effects of reactive oxygen species. Loss of KGF, was previously described to be reduced in diabetes wound and was linked to a loss of wound contraction, that was relevant in a human model 31 in which KGF promotes fibroblasts contraction increasing the expression of TGF beta1 and Smad pathway.…”
Section: Discussionmentioning
confidence: 90%
“…The area of the gels observed from above was measured in the ImageJ program and compared between groups. This method is similar to Ehrlich and Moyer () and Peng, Wu, Tang, Li, and Peng ().…”
Section: Methodsmentioning
confidence: 93%